Epizootiologic Monitoring of Natural Focus of Tularemia in the Stavropol Region in 2010-2017 - E. V. Gerasimenko; N. V. Tsapko; O. A. Gnusareva; G. P. Shkarlet; O. A. Belova (Проблемы особо опасных инфекций, 2020)
Objective of the study was an assessment of the current epizootiological situation on tularemia in the Stavropol Region. Materials and methods. Processed were the data of laboratory investigations of the field material over the period of 2010-2017. All field samples were studied in the laboratories of the Stavropol Anti-Plague Institute using PCR and bioassay. Results and discussion. This paper presents the analysis of the epizootiological situation for the period of 2010-2017 in the Stavropol Region. The species composition and the number of the main carriers of tularemia have been established. Epizootic activity of the focus is defined by mice of the genus Sylvaemus. Data on the isolation of strains from ticks, small mammals and environmental objects are presented and processed. According to our studies, over the past seven years, infection with tularemia agent has been detected in seven species of mammals: S. uralensis, Microtus arvalis, M. socialis, Mus musculus, Crocidura suaveolens, Erinaceus roumanicus, Lepus europaeus. For the period of epizootic monitoring between 2010 and 2017 37 strains of the causative agent were isolated from small mammals - 12 (32.4 %), ectoparasites - 9 (24.3 %), and environmental objects - 16 (43.2 %). All isolated strains have been identified as Francisella tularensis holarctica biovar II, eryR.